Role of computed tomography in the determination of resectability of carcinoma pancreas - Sasikumar, M. N.; Salam A., Chintha (International Surgery Journal, 2019)
Background: Pancreatic cancer is one of the most aggressive neoplastic processes. Inspite of progress in the diagnosis and treatment of malignancies, the resectability and survival rates for pancreatic cancer are very poor. This study aims to determine the accuracy of computerised tomography in assessing the resectability of carcinoma pancreas. Methods: 66 patients with carcinoma pancreas, who were judged fit for surgery were studied. All cases had undergone preoperative contrast enhanced triphasic computed tomography (CT) for assessing the resectability. Radiological data was compared with per operative findings for assessments regarding vascular invasion and resectability. Results: Of the 66 cases, resectability reported by CT was 59 (89.4%). The rest of 7 (10.6%) cases were reported as unresectable. Per operatively vascular involvement was found in 14 (21.2%) cases and with no vascular invasion in 52 (78.8%) cases. All the unresectable cases reported in CT (7 cases) turned out to be unresectable. Out of 59 cases reported as resectable, 43 (65.2%) cases under went Whipples procedure, while rest of the 23 (34.8%) cases underwent palliative procedures. Out of these 23 cases, 14 (21.2%) cases were unresectable due to vascular involvement. Conclusions: The study has shown that CT does assess the operability in carcinoma pancreas, assessing mainly unresectability though less effective in assessing resectability. The role of endoscopic ultrasound and laparoscopic ultrasound in aiding CT in further assessment of resectable and borderline resectable cases are to be considered for further research.